2014
DOI: 10.1116/1.4857295
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized laminin concentration gradients on electrospun fiber scaffolds for controlled neurite outgrowth

Abstract: Neuronal process growth is guided by extrinsic environmental cues such as extracellular matrix (ECM) proteins. Recent reports have described that the growth cone extension is superior across gradients of the ECM protein laminin compared to growth across uniformly distributed laminin. In this work, the authors have prepared gradients of laminin on aligned electrospun nanofibers for use as substrates for neuronal growth. The substrates therefore presented both topographical and chemical guidance cues. Step gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As mentioned earlier, self-assembling peptide nanofiber gels now provide independent control on the matrix stiffness (Sur et al, 2013 ). Effects of topography (maybe also matrix stiffness) and of haptotactic cues can also be compared in 3D by culturing cells on an electrospun nanofiber gel with a gradient of surface-bound laminin (Zander and Beebe, 2014 ). When the gradient was parallel to the nanofibers, PC12 neurites grew preferentially up the laminin gradient; however, when the gradient was imposed in the perpendicular direction, they were unaffected.…”
Section: Combining Mechanical and Biochemical Stimulimentioning
confidence: 99%
“…As mentioned earlier, self-assembling peptide nanofiber gels now provide independent control on the matrix stiffness (Sur et al, 2013 ). Effects of topography (maybe also matrix stiffness) and of haptotactic cues can also be compared in 3D by culturing cells on an electrospun nanofiber gel with a gradient of surface-bound laminin (Zander and Beebe, 2014 ). When the gradient was parallel to the nanofibers, PC12 neurites grew preferentially up the laminin gradient; however, when the gradient was imposed in the perpendicular direction, they were unaffected.…”
Section: Combining Mechanical and Biochemical Stimulimentioning
confidence: 99%
“…Therefore, the plasma treatment has the main impact on decrease in hydrophobicity of SF/PEO scaffolds compared to LN functionalization. It was suggested that the plasma treatment of SF/PEO nanofibers cause partial decomposition of the scaffolds surfaces and induce O‐containing functional groups such as hydroxyl and carboxylic acid groups . These induced carboxylic acids alongside the aspartic (Asp) and glutamic (Glu) acids of SF could bind to the amine groups of LN and form amide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…LN, one of the major components of ECM basement membrane, is a family of heterotrimeric glycoproteins (500–1000 kDa) which includes multi‐domain “cross‐like” structure of three polypeptide chains (i.e., a, b, and c) which characterize the functions and properties of the LN . LN contains the well‐characterized peptide sequences of RGD (Arg‐Gly‐Asp) and YIGSR (Tyr‐Ile‐Gly‐Ser‐Arg) presented in a‐chain, which has the function of promoting cell adhesion and migration, as well as the sequence of IKVAV (Ile‐Lys‐Val‐Ala‐Val) which is presented near the C‐terminal end of a1‐chain and promote neurite outgrowth . In addition to the capability of LN to modulate cell adhesion and stimulate neurite growth through its specific peptide sequences, it can essentially contribute in integrin signaling .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel nontoxic and biocompatible inorganic-based materials have also been examined and explored as a desirable alternative [ 20 ]. Among several methods for the preparation of ECM-mimicking scaffold materials [ 12 , 21 ], electrospinning is a convenient technique typically used in the preparation of nanofibers for in vitro experiments [ 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. However, if materials need to be mass produced for clinical use, other possible methods such as pressure-coupled infusion gyration [ 31 ] can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the proliferation of Schwann cells on the laminin-modified PCL-chitosan nanofiber substrate was tracked for 4 days [ 25 ], and on a laminin-modified PLCL core-shell nanofiber substrate for 7 days [ 26 ]. The neurite extensions of neuron-like PC12 cells on laminin-modified PLLA nanofiber substrates were observed for 5 days [ 27 ], and on a covalently-bonded laminin-PCL nanofiber for 10 days [ 28 ]. The neurite extension of DRG on a laminin-PCL blend nanofiber was traced for 4 days [ 29 ] and on a laminin-modified PLLA nanofiber for 6 days [ 30 ].…”
Section: Introductionmentioning
confidence: 99%